The essence of case on the merits consideration stage in administrative proceedings - N. V. Ilchyshyn (Bulletin of Kharkiv National University of Internal Affairs)
Study of the administrative proceedings order of implementation as a whole involves the determination of the essence of individual stages of such proceedings. The stage of consideration of the case on the merits due to the specificity of the procedural actions involves a number of both procedural actions designed to ensure a full and impartial clarification of the truth in the dispute, as well as compliance with certain issues of the traditionality of the court session. In other words, consideration of the case on its merits is usually carried out within the framework of a court session, which is characterized as the procedural activity of almost all participants in the process, without exception, in one place. This allows for a more qualified (availability of experts and specialists) and objective (possibility to ask participants questions) assessment of the entire evidence base and to reach certain conclusions. The subject of the research is the norms of the current legislation and the scientific views of famous scientists regarding the meaning and content of such a stage as consideration of the case on its merits.